Analysis of Transportation Mode Selection at Padjadjaran University Campus Jatinangor Using Fuzzy Analytic Hierarchy Process (FAHP) Method - Bhagawanta, Hanif Ibnu; Hertini, Elis; Nahar, Julita (International Journal of Global Operations Research, 2023)
Transportation has become a very attached part of human daily life as a means of mobility in activities. Each transportation user has their own goals in transportation, so the mode of transportation travel takes effect in making it easier for users to reach their goals. At Padjadjaran University, Campus Jatinangor, there are several alternative modes of transportation, namely Odong-Odong, Easy Bike, conventional motorcycle taxis, and online motorcycle taxis. Each alternative mode of transportation has varying characteristics and user needs, so it is necessary to make the right decision. This study uses the Fuzzy Analytic Hierarchy Process (FAHP) method to determine priority criteria and alternative modes of transportation suitable for use on campus. The criteria used in this study include tariff, time, comfort, safety, and environmental responsibility. The results in this study obtained the order of priority criteria, is safety, comfort, time, tariff, and environmental responsibility. Moreover, the alternative priority orders are Odong-Odong, online motorcycle taxis, Easy Bike, and conventional motorcycle taxis. That can be interpreted as the safety criteria are the most considered, and Odong-Odong is the most appropriate alternative to be used at Padjadjaran University, Campus Jatinangor.